Plasminogen activator of islets of Langerhans: modulation by glucose and correlation with insulin production. - Virji, M A (1980)
Islets of Langerhans isolated from rat pancreas contain and secrete plasminogen activator (PA). Production of PA is increased up to 15-fold by culture in the presence of high concentrations of glucose, and the dose-response curves for the effect of glucose on secretion of PA and on insulin are superimposable. Alloxan, a diabetogenic agent that is selectively cytotoxic for beta cells, abolishes the PA response to glucose. Various agents and hormones that affect beta-cell function affect the secretion of PA in a manner parallel to their modulation of insulin secretion. These observations suggest that PA is produced by beta cells and that enzyme synthesis and secretion are regulated in concert with those of the hormone. The potential role of PA and of plasmin in the physiology of the islets is considered. In particular, because plasmin cleaves proinsulin to a product that is electrophoretically indistinguishable from insulin, it is suggested that the PA/plasmin system may play a part in the conversion of proinsulin to the active hormone.